Penerapan Target Costing dalam Pengelolaan Biaya Produksi untuk Optimalisasi Laba - Eza Gusti Anugerah; Nining Ika Wahyuni; Imam Mas'ud (e-Journal Ekonomi Bisnis dan Akuntansi, 2017)
The purpose of this research is to study how Target Costing implementation on managing production cost in Tape ProducerSumber Madu, in order to reach the desired proftt. The difficulties on managing cost and getting desired profit in SumberMadu was the reason and motivation behind this research. To get all the data that needed in this research, researcher chooseto do observation and interviewing the production manager and the owner of Sumber Madu. The production cost calculatedby Sumber Madu and the Alternative production cost calculated by researcher, were analyzed and compared each other toknow how good the Target Costing implementation in Sumber Madu. The result of this research shows that Target CostingImplementation in Sumber Madu was good and fit. Implementation of Target Costing can raise the profit earned as much asthe desired profit. And then, Sumber Madu can manage the production cost on its product.